Description of two new species of the genus Megophrys (Amphibia: Anura: Megophryidae) from Heishiding Nature Reserve, Fengkai, Guangdong, China, based on molecular and morphological data - Li, Yu-Long; Jin, Meng-Jie; Zhao, Jian; Liu, Zu-Yao; Wang, Ying-Yong; Pang, Hong (Zootaxa, 2014)
Two new species, Megophrys acuta sp. nov. and Megophrys obesa sp. nov., are described based on a series of specimens collected from Heishiding Nature Reserve, Fengkai County, Guangdong Province, China. They can be distinguished from other known congeners occurred in southern and eastern China by morphological characters and molecular divergence in the mitochondrial 16S rRNA gene. M. acuta is characterized by small and slender body with adult females measuring 28.1–33.6 mm and adult males measuring 27.1–33.0 mm in snout-vent length; snout pointed, strongly protruding well beyond margin of lower jaw; canthus rostralis well developed and sharp; hindlimbs short, the heels not meeting, tibio-tarsal articulation reaching forward the pupil of eye. M. obesa is characterized by stout and slightly small body with adult females measuring 37.5–41.2 mm, adult male measuring 35.6 mm in snout-vent length; snout round in dorsal view; canthus rostralis developed; hindlimbs short, the heels not meeting, tibio-tarsal articulation reaching forward the posterior margin of eye. The discovery of these two new species further confirms that the diversity of this genus has been significantly underestimated. At present the genus Megophrys contains 56 species of which 35 species are distributed in China.